Prevalence of Helicobacter Pylori Infection in Children and Adolescents - Mahmoud Al-Hosni; Malak Adel Alsheikh; Malak Meloud Elhasady (African Journal of Advanced Pure and Applied Sciences, 2023)
Background: The prevalence of Helicobacter pylori has declined over recent decades due to improved sanitation, socioeconomic development, and better living conditions; however, its prevalence remains high in the developing world H. pylori has infected nearly 50% of the population worldwide, with rates of 35%–90% depending on population diversity and geographic area. Objectives: The objectives of this study are to study the H. pylori infection to children by identifying seroprevalence of H. pylori in pediatric patients. Material and Methods: The data was collected from the records of privet lab in Derna city where the sample collected from children who came to the in order to investigate for H.pylori infections. Results: Total, 200 children—89 boys (44.5%) and 111 (55.5%) girls were enrolled in the study. Of the 200 children studied, 167 (83.5%) were living in Derna (urban area) and 33 (16.5%) in Umarzam, Alqba and AinMarah (rural area), 12(6.0%) in Umarzam, 13(6.5%) in Alqba and 8(4%) in Ainmarah. The overall prevalence of H. pylori infection in children was 37.5% Conclusion: This infection is largely acquired during early childhood and the infection increased with age. Traditional diagnostic tools such as endoscopy and serology can be too invasive for children noninvasive urea breath test Analyzed group included 111 girls and 89 boys between 3years and 15years (mean age 9).